Do IMF and World Bank influence voting in the UN General Assembly? - Axel Dreher; Jan-Egbert Sturm (Center for Economic Studies and ifo Institute (CESifo), 2006)
Using panel data for 188 countries over the period 1970-2002 this paper empirically analyzes the influence of the IMF and the World Bank on voting patterns in the UN General Assembly. Countries receiving adjustment programs and larger non-concessional loans from the World Bank vote more frequently in line with the average G7 country. The same is true for countries obtaining non-concessional IMF programs. Regarding voting coincidence with the US, World Bank (concessional and non-concessional) loans have a significant impact, while the IMF has not. These results are robust to the inclusion of control variables and method of estimation.
Keywords: F33; 330; Wahlverhalten; Anpassungsprogramm des IWF; Internationaler Kredit; Panel